Test First Model for Application in the Academic Setting - Normi Sham Awang Abu Bakar; Norzariyah Yahya (Bulletin of Electrical Engineering and Informatics, 2018)
This research elaborates the selection of the Test First and Test Last model for a pilot experiment that was executed as a feasibility study to validate the suitability of the existing Test First model for its implementation in the series of actual experiment. The series of actual experiment is designed to investigate the quality of the project developed by the students in higher educational institution with the Test First over Test Last model. The findings gathered from the pilot experiment demonstrate that there were misunderstandings on the user stories among the participants that have led to the development of an enhanced Test First model.